Experimental Evidence on Returns to Capital and Access to Finance in Mexico - McKenzie, David; Woodruff, Christopher (World Bank, 2012)
A strong theoretical argument for focusing on access to finance is that financial market imperfections can result in large inefficiencies, as firms with productive investment opportunities underinvest. Lack of access to finance is a frequent complaint of microenterprises, which account for a large share of employment in developing countries. However, assessing the extent to which a lack of capital affects their business profits is complicated by the fact that business investment is likely to be correlated with a host of unmeasured characteristics of the owner and firm, such as entrepreneurial ability and demand shocks. In a randomized experiment that gave cash and in-kind grants to small retail firms, providing an exogenous shock to capital, the shock generated large increases in profits, with the effects concentrated among firms that were more financially constrained. The estimated return to capital was at least 20–33 percent a month—three to five times higher than market interest rates.